A SEMIOTIC ANALYSIS OF THE SELECTED POEM IN RUPI KAUR’S MILK AND HONEY - Br Karo Sekali, Tria Novita; Tarihoran, Rezky Khoirina (Fakultas Sastra UMN AL Washliyah, 2025)
This research aims to analyze the semiotic elements in Rupi Kaur’s poetry collection Milk and Honey by applying Ferdinand de Saussure’s semiotic theory. The objectives of the study are to identify the signifiers and the signifieds in ten selected poems and to explain the messages conveyed through their interaction. This study uses a descriptive qualitative method combined with content analysis to examine how meaning is constructed through the relationship between visual illustrations and poetic texts. The data were collected using literature study and purposive sampling. Ten poems were selected based on their thematic representation across the four main sections of the book: The Hurting, The Loving, The Breaking, and The Healing. The findings reveal that each poem contains unique visual and verbal sign systems that reflect emotional experiences, identity, trauma, love, and personal growth. The interaction between signifier and signified in each poem contributes to the overall meaning and message, illustrating the depth and complexity of the poet’s expression.